Synthesis of oligodeoxyribonucleotide N3'-->P5' phosphoramidates. - Chen, J K (1995)
An efficient synthesis of the novel nucleic acid analogs oligodeoxyribonucleotide N3'-->P5' phosphoramidates, where the 3'-oxygen is substituted by a 3'-nitrogen, is described. Synthesis of the title compounds was accomplished by the following synthetic steps. First, 5'-O-DMT base-protected-3'-amino-2',3'-dideoxynucleosides were prepared. The 3'-aminopyrimidines were obtained via the corresponding 2,3'-anhydronucleosides, whereas 3'-aminopurines were derived via 2'-deoxyxylo precursors. Second, using the prepared 3'-aminonucleosides, oligonucleotide N3'-->P5' phosphoramidates were synthesized on a solid support. Oligonucleotide chain assembly was based upon a carbon tetrachloride-driven oxidative coupling of the appropriately protected 3'-aminonucleosides with the 5'-H-phosphonate diester group, resulting in the formation of an internucleoside phosphoramidate link. Fully deprotected oligonucleotide N3'-->P5' phosphoramidates were characterized by ion exchange and reversed phase HPLC, capillary and slab gel electrophoresis and by 31P NMR analysis. Oligonucleotide N3'-->P5' phosphoramidates form remarkably stable duplexes with complementary RNA strands and also with themselves, where the melting temperature of the complexes exceeded that for the parent phosphodiester compounds by 26-33 degrees C. Additionally, duplexes formed by oligonucleotide phosphoramidates with single-stranded DNA were also more thermally stable than those formed by phosphodiesters. The described properties indicate that these compounds may have great potential in oligonucleotide-based diagnostics and therapeutic applications.